2022
DOI: 10.3390/agronomy12081893
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Ecology and Agronomy to Foster Diverse Pastures and Healthy Soils

Abstract: Renovating pastures to increase forage species diversity is a burgeoning practice among producers. Over a century of grassland and small-plot research suggests that increasing plant diversity can lead to improved pasture productivity, resilience, and soil health. However, it remains hard to decipher how these benefits translate to grazed production systems given the limited experimentation in realistic grazing systems. There is a disconnect between ecological and agronomic research regarding what qualifies as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The high or low diversity of a species in a vegetation community depends on the number of individuals of each species present (Susanti et al 2021). The similar indication of the increase of diversity index and the age of oil palm plantations shows that the more similar the number of individuals between species or the more evenly distributed they are, the greater the balance which is indicated by the increasing diversity index (Reed & Morrissey 2022).…”
Section: Plant Diversitymentioning
confidence: 97%
“…The high or low diversity of a species in a vegetation community depends on the number of individuals of each species present (Susanti et al 2021). The similar indication of the increase of diversity index and the age of oil palm plantations shows that the more similar the number of individuals between species or the more evenly distributed they are, the greater the balance which is indicated by the increasing diversity index (Reed & Morrissey 2022).…”
Section: Plant Diversitymentioning
confidence: 97%
“…(1) Forage quality and animal performance [17][18][19][20] (2) Animal grazing behavior [21] (3) Fatty acid (FA) profiles of various forages [22,23] (4) Ecosystem health for production animals [24][25][26] (5) Technology for improving management [27] 2.1. Forage Quality and Animal Performance Tracy et al [17] found that adding nutritionally high-quality, summer-productive forages, such as alfalfa (Medicago sativa) or sericea lespedeza (Lespedeza cuneata (Dum.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Reed and Morrissey [26] reviewed the scientific literature examining the current state of research regarding plant diversity and its potential benefits for soil health in pasture. Increasing pasture species diversity is a practice that is increasingly used by producers.…”
Section: Ecosystem Healthmentioning
confidence: 99%
“…Legumes used as cover crops can also boost the availability of organic carbon and nitrogen (Balota et al., 2014; Verzeaux et al., 2016). Cover crops can have positive effects on multiple soil health indicators, but multi‐species cover crop mixes do not necessarily improve them better than one specie cover crop (Decker et al., 2022; Florence & McGuire, 2020; Reed & Morrissey, 2022). Moreover, cover crops can influence the soil microbiome.…”
Section: Introductionmentioning
confidence: 99%